2016
DOI: 10.1177/2229411220160303
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Body Mass Index and Dental Caries in Patients Attending Baqai Dental College, Karachi, Pakistan

Abstract: The aim is to correlate the relationship between body mass index (BMI) and dental caries in patients attending Baqai Dental College, Karachi, Pakistan. Materials and Methods: This cross-sectional study was conducted in the Department of Operative Dentistry, Baqai Dental College, between June 1 st , 2014 and March 1 st , 2015. A simple random technique was employed and 200 adult patients, aged 18-35 years were selected to participate in the study. A structured questionnaire was designed to gather information on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…The results of our study were in accordance with Marshall et al [21] who were "obesity increases the risk of caries" nor "caries increases risk of obesity, " but rather a common risk factor increased the likelihood of both diseases. Wali et al [22] found a positive correlation between dental caries and BMI.…”
Section: Discussionmentioning
confidence: 96%
“…The results of our study were in accordance with Marshall et al [21] who were "obesity increases the risk of caries" nor "caries increases risk of obesity, " but rather a common risk factor increased the likelihood of both diseases. Wali et al [22] found a positive correlation between dental caries and BMI.…”
Section: Discussionmentioning
confidence: 96%
“…A study done by Wali A (2016) reported a statistically significant correlation between BMI and DMFT scores which may be due to the patients having irregular dietary pattern, lack of knowledge of oral hygiene and infrequent visits to dentist. 21 However, not all studies have found a positive correlation between BMI and dental caries; some studies suggest that there is no relationship between BMI and dental caries e.g. Macek and Mitola (2006) 22 , Sadeghi M (2007) 23 , Almerich-Torres T (2017) 11 and others showed an inverse relationship e.g.…”
mentioning
confidence: 99%